Electrocardiographic characteristics, anthropometric features, and cardiovascular risk factors in a large cohort of adolescents. Issue 11 (23rd April 2018) - Santini, Massimo; Di Fusco, Stefania Angela; Colivicchi, Furio; Gargaro, Alessio
Abstract: Aims: The characteristics of electrocardiographic (ECG) patterns in the general population of adolescents are insufficiently defined. The purpose of this study is to report ECG patterns and their association with anthropometric characteristics. Methods and results: Twenty-four thousand and sixty-two students of Roman schools, aged 12–19, were screened with ECG and physical examinations. Electrocardiographic abnormalities were classified as either minor/non-clinically relevant or major, and anthropometric measures were evaluated per age class. Obesity prevalence was 20.9%, with a higher rate in younger students ( P  < 0.008 for all comparisons, except for the pair 16–17 vs. 18–19 years). Stage 1 hypertension was found in 3.14% of adolescents, Stage 2 hypertension in 0.45% of adolescents, and isolated systolic hypertension in 11.7% of adolescents. Heart rate and QT interval corrected for heart rate (QTc) decreased with increasing age. The QTc was longer in females than in males over 14 years. A higher rate of incomplete right bundle branch block (RBBB) was observed in underweight students (21.58% vs. 15.10% in non-underweight students, P  < 0.0001). Complete RBBB was the most common major ECG abnormality (1.6%). It was associated with height irrespective of age, sex, and body mass index (odds ratio 17.9; 95% confidence interval 5.0–64.6) and more frequent in students regularly practicing physical activity (1.80% vs. 1.02%, P  = 0.0009). Conclusion: Heart rate and QTc decreased with increasing age. The QTc was longer in females than in males over 14 years. RBBB was the most common major abnormality and was associated with higher stature. The prevalence of some cardiovascular risk factors in adolescents is provided.